Adsorption of Fuchsin Basic on Copper in Citric Acid - J.L. Polo; E. Cano; P. Pinilla; J.M. Bastidas (Adsorption Science & Technology)
The adsorption of Fuchsin Basic (FB) on copper surfaces in citric acid solutions whose concentrations ranged from 0.001 to 0.1 M was investigated using gravimetric measurements. The concentrations of FB studied ranged from 1 × 10 −5 to 1 × 10 −1 M with adsorption experiments being conducted at temperatures from 298 K to 328 K. The adsorption mechanism is discussed in terms of the applicability of the conventional Frumkin, Bockris–Swinkels and Kastening–Holleck isotherms, amongst others. The best fit was obtained using the Frumkin isotherm model. A thermodynamic/kinetic model of adsorption was also fitted.